Pulmonary oedema during treatment of acute water intoxication. - Maclean, D. (BMJ Group, 1976)
Acute water intoxication with deepening coma and uncontrolled epileptiform seizures in a 25-year-old previously fit male schizophrenic was treated with hypertonic (2 N) saline and a 20% mannitol solution. This improved his neurological state but precipitated severe pulmonary oedema. Intravenous frusemide increased his urinary output sufficiently to clear the pulmonary oedema. In acute water intoxication the use of hypertonic solutions may thus precipitate left heart failure by expanding the intra-pulmonary blood volume beyond the capacity of even a healthy left ventricle to compensate. Simple water restriction will produce a slower but perhaps safer improvement.